Mengenal Multi Dimensional Scaling - Muhammad Idrus (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2006)
Measurement of psychological attributes is an important aspect in Psychology. Related with that, the application of measurement tools-including tests scaling become important. So far, Most of psychological scales apply uni-dimensional scaling model which is not sufficient to measure double or even multi-dimension of psychological attributes basically. Therefore, it is necessary to apply multidimensional scaling model in psychological measurement. Multidimensional Scaling (MDS) is a method to represent distance distinction of similarity or unsimiliarity between objects. MDS interlace with the situations where the stimulus is various with some dimensions simultaneously. Some methods in MDS including: the method of triads, complete methods of triads, the methods of tetrads, the method of multidimension rank-order, the method of multidimensional successive categories and the method of confusion.Keywords: Multidimensional scaling, uni-dimensional scaling